Transforming waste to catalyst: utilizing incineration ash for environmental solutions - Liu, Zheng (Nanyang Technological University, 2024)
Nowadays, air pollution is a main problem which harms humans. The transportation source is a major source of waste gas pollution. The main pollutants from transportation emission are carbon monoxide (CO), in-completely combusted hydrocarbons (HC), nitrogen oxides (NOx) and small particles. These exhaust air pollutions are hazard and become a pressing problem for humans. For instance, more than 90% outdoor CO emission in urban area was from vehicle emission. Breathing CO can cause headache, dizziness, vomiting and nausea, even death. Exposure to moderate and high levels of CO over long periods of time has also been linked with increased risk of heart disease. People who survive severe CO poisoning may suffer long-term health problems. Incineration ash, a by-product of waste-to-energy processes, is an extraordinarily complex material that contains a wide range of chemical species. Instead of landfill, recent studies have shown that incineration ash can also be a potential source of valuable metals and catalytic materials. The thesis aims to develop innovative, low cost and environmentally friendly catalytic materials to convert those exhaust waste gas like CO. The main CO catalyst in market is Au-based materials and Pt-based materials. The project finds that the incineration bottom ash (IBA) and incineration fly ash (IFA) could be catalyst for CO and NOx as they contain some noble metal like Au and Pt which is catalyst of oxidizing and reduction reaction. The main applications of IBA and IFA in market are bulk fill, asphalt via re-melting at 1200°C, cement bound materials and pavement concrete. There is also a large amount of IBA and IFA treated by landfill which is a kind of energy waste. If either IBA or IFA can be used as catalytic materials, it will not only help disposal those hazard ash, but help reduce the waste gas pollution of engine emission. Incineration ash was treated with some physical and chemical methods to remove some toxic and noncatalytic elements. The modification was included with drying, sieving, milling, acid-washing, water-washing, and some other processes. The treated precursor was sintered at 1100°C and shaped to specific ceramic substrates. After measuring CO catalytic tests, it was estimated that the ceramic blocks made by incineration ash had good oxidation catalytic performance under 500°C, which average CO catalytic performance of IBA from TIP and TSIP was 15.3% and 17.8%, average CO catalytic performance of IFA from TIP and TSIP was 18.1% and 8.2%, and it of IBA from REMEX is 9.9%. Machine learning model had been used to analyze the catalytic performance with some characterization data and it is used to predict the catalytic performance in the future. Meanwhile, the new application of incineration ash, three-way catalytic ceramic substrate is discussed. Incineration ash has shown promising catalytic performance in various chemical reactions. The catalytic properties of incineration ash can be attributed to the presence of metal oxides, such as calcium oxide, magnesium oxide, and iron oxide, which can function as active sites for catalytic reactions. Overall, the use of incineration ash as a catalyst offers a sustainable and cost-effective solution for waste management while also contributing to the development of green chemistry. Further research is needed to optimize the catalytic performance of incineration ash and to explore its potential applications in various industrial processes.